Vergisson 4: a left‐handed Neandertal. Issue 1 (21st September 2016) - Condemi, Silvana; Monge, Janet; Quertelet, Sylvain; Frayer, David W.; Combier, Jean
Abstract: Objectives: Handedness is an important marker for lateralization of humans in the modern and fossil record. For the most part, Neandertals and their ancestors are strongly right‐handed. We describe a single tooth from a Neandertal level at Vergisson 4 (Vg 4‐83). This left upper central incisor shows all the features typical of Neandertal incisors. It also exhibits a predominance of left‐handed striations. Methods: Striations on the incisor's labial surface were mapped at 20x magnification using Photoshop. Angulations of the striations were determined from their deviation from the maximum mesio‐distal line and were analyzed using NIH's freeware, Image J. Results: Of the 60 labial surface striations, Vg 4‐83 shows a strong predominance of left‐handed striations (46; 76.7%), which are statistically significantly different ( p < .001 with a two‐tailed chi 2 test) from the small number (3) of right‐handed striations. Discussion: The identification of another left‐handed Neandertal adds to our understanding about handedness variation in this fossil hominin. Given the high frequency of right‐handed Neandertals, the 90: 10 modern ratio is still preserved in this group.